Go cheng xu she ji yu yan / The Go programming language / Alan A.A. Donovan, Brian W. Kernighan. - Donovan, Alan A. A., 1976-; Kernighan, Brian W. (Ji suan ji ke xue cong shu., 2021)
Detailed summary in vernacular field.